Some Aspects of 20th Century Art. - Read, Herbert (London : Marlborough Fine Arts Ltd., 1961)
Armitage, Kenneth ; Balla, Giacomo ; Baumeister, Willi ; Chadwick, Lynn ; Dubuffet, Jean ; Ernst, Max ; Feininger, Lyonel ; Francis, Sam ; Gleizes, Albert ; Gris, Juan ; Klee, Paul ; Lanskoy, André ; Leger, Fernand ; Mathieu, Georges ; Metzinger, Jean ; Miro, Joan ; Mondriaan, Piet ; Moore, Henry ; Picasso, Pablo ; Pollock, Jackson ; Riopelle, Jean-Paul ; Schwitters, Kurt ; de Staël, Nicholas ; Tàpies, Antoni ; Vieira da Silva, Maria Elena
biografie
Some Aspects of 20th Century Art, Marlborough Fine Arts Ltd., London, July - August 1961
Engels
boek